Novel Cell Therapy Using Mesenchymal Stromal Cell Sheets for Medication-Related Osteonecrosis of the Jaw - Kaibuchi, Nobuyuki; Iwata, Takanori; Koga, Yoko Kawase; Okamoto, Toshihiro (Frontiers in Bioengineering and Biotechnology, 2022)
Since the first report of medication-related osteonecrosis of the jaw (MRONJ) in 2003, various studies have been conducted. However, the optimal treatment and prevention of MRONJ are not clear. As a result, dentistry, oral surgery, and departments involved in the treatment of cancer and bone diseases are struggling with the management of MRONJ. Several cases of MRONJ cannot be cured by conventional treatment strategies, as recommended in various position papers. Therefore, several studies have been conducted to investigate the efficacy of novel therapies for MRONJ. However, no definitive treatment has been determined. Several cell therapies for MRONJ have been reported. 10 animal studies and 5 case reports have described autologous cell transplantation in MRONJ patients. Although these reports show the efficacy of cell therapy for MRONJ, the efficacy of cell therapy for MRONJ has not been established due to the lack of large, statistically accurate clinical trials. We have been investigating the efficacy of MRONJ treatment using mesenchymal stromal cell (MSC) sheets since 2013 and confirmed its efficacy through various experiments in which MSC sheets were transplanted into model rats and beagle dogs with MRONJ-like lesions. Based on these results, we are planning to conduct clinical trials of MRONJ therapy using periodontal ligament-derived MSC sheets.